Development and Validation of the New Environmental Locus of Control (NE-LOC) Scale: A Novel Measure of Internal, External, and Community Locus of Control for Sustainability - Guazzini, Andrea; Baroni, Marina; Fiorenza, Maria; Sprugnoli, Sofia; Valdrighi, Giulia; Duradoni, Mirko (Sustainability, 2025)
The promotion of sustainability, especially with regard to social and urban sustainability (e.g., well-being and neighborhood revitalization), is mainly linked to human activities and behaviors. Notably, pro-environmental behaviors and actions that promote sustainability depend on the degree to which the individual attributes responsibility, namely, internal and external environmental locus of control (E-LOC). Moreover, from a collectivist perspective, the well-being of communities may also depend on their ability to take action to achieve sustainability goals. In keeping with this, we conducted two different studies to develop and validate (internally and externally) a new instrument that is able to assess internal and external E-LOC by also capturing a third dimension in respect of community E-LOC. In the first study, we performed exploratory factor analysis (EFA) by collecting data from 694 subjects (55.3% cis females; mean age = 30.1, sd = 12.6). In the second study, we conducted confirmatory factor analysis (CFA) on a sample of 1.852 subjects (57% cis females; mean age = 27.6, sd = 11.4), which demonstrated an adequate fit to the theorized model. The final form of the instrument comprises nine items subdivided into internal, external, and community NE-LOC factors. Moreover, the results pointed out significant correlations between the NE-LOC scale and engagement in pro-environmental behaviors and attitudes, pro-environmental self-identity, readiness to change for sustainability, and eco-anxiety. Therefore, the NE-LOC scale can be considered a suitable instrument for the assessment of internal and external NE-LOC, as well as to measure the attribution of collective environmental responsibility.